Tipología de los sistemas vocálicos románicos - Portilla Chaves, Mario (Universidad de Costa Rica, 2015)
A synchronic classification of the vowel systems of the Romance languages is proposed, based on the Prague School's distinctive features analysis.Maintenance (or innovation) of distinctive features from Low Latin allows delimiting the three areas of distribution of these systems in Europe.Eastern Romania includes Rumanian and presents innovation of central vowels. Northern Rumania covers French, Provencal, Rheto Romance and Gallic-Italic dialects and includes innovation in rounded front vowe1s, Southern Romania groups Dalmatian, Italian, Sardinian, Catalan, Spanish and Portuguese and lacks innovative vowels.